FIST -INTeRC strategic partnership in advance material R&D MoU signing - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
KOTA KINABALU June 7, 201 l.A MoU on advanced material research cooperation has been signed between FIST and Industrial Nanotechnology Research Center, SIRIM Berhad.